PENEGAKAN HUKUM PEMERINTAH DALAM PENGELOLAAN SAMPAH DI KOTA PEKANBARU TAHUN 2019 - ", Widiawati; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Writing a thesis entitled "Government Law Enforcement in Waste Management in Pekanbaru City in 2019". Law enforcement is the process of making efforts to enforce or actually function legal norms as guidelines for behavior in traffic or legal relations in social and state life. Waste management is a systematic, comprehensive, and sustainable activity that includes waste reduction and handling, aimed at improving public health and environmental quality and making waste a resource. This research was conducted at the Department of Environment and Cleanliness of Pekanbaru City. The purpose of this study is to describe Government Law Enforcement in Waste Management in Pekanbaru City in 2019. The theory used is the theory of Gustav Radbruch, namely the elements of law enforcement and Soerjono Soekanto's theory, namely the factors of law enforcement. The research method used is descriptive qualitative with data collection techniques through interviews and documentation, the type of data used is secondary data and primary data. The final conclusion from this research is that the implementation of law enforcement has not been optimally carried out by the Pekanbaru City Government because it is influenced by several factors.Keywords: Enforcement, Waste Management, Sanctions